UJI KOEFISIEN FENOL FORMULASI DESINFEKTAN DENGAN VARIASI KONSENTRASI BENZALKONIUM KLORIDA - Nurmaya Effendy (As-Syifaa Jurnal Farmasi, 2009)
A research on The Phenol Coefficient Test Formulation of Disinfectant with vary Concentration Of Benzalkonium Chloride to microorganisms test Salmonella thyposa and Staphylococcus aureus ATCC 25922 has been done. This research was conducted to know concentration of  solution disinfectant with certain dilution which effective to destroy the pathogen microorganisms. Microbiology’s test was done with dilution methods to know dilution lower which can delay the growth of test microorganisms and Coefficient Phenol methods (Rideal-Walker Test) to know dilution of disinfectant which concentrate on five variations such as benzalkonium chloride, 0.05%; 0.1%; 0.2%; 0.4%; 0.8%, with used NB media (Nutrient Broth) which incubated for 2 x 24 hours. Result of research show that count of phenol coefficient every that concentration of Benzalconium chloride are 0.4; 0.8; 1.4; 2.2; 5.4 for Salmonella thyposa and 0.4; 0.8; 1.6; 5.4; 11.8 for Staphylococcus aureus ATCC 25922. Because count of coefficient phenol are large than 0.05 according to the appointment of Ditjen POM, and then formula which standarized can as desinfectant. From dilution and properties of antimicrobe, that benzalkonium chloride 0.8% with dilution 1:108 that is very effective to two that pathogen bacteries to be as an used active agent disinfectant floor cleaner.Keywords : Phenol coefficient test, benzalkonium chloride, disinfectant, floor cleaner